Competition or Collusion? Negotiating Discounts Off Posted Prices - Alexander Raskovich (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2006)
Opportunities for buyers to negotiate discounts can blunt competition in the initial posting of prices. It is always an equilibrium for identical suppliers to post price at the common marginal cost. If few buyers have opportunities to bargain, this equilibrium is unique. If many buyers have bargaining opportunities, however, a second equilibrium emerges in which suppliers post the monopoly price and then negotiate discounts individually with buyers. In this equilibrium, discounted prices are above marginal cost and profits increase with concentration. Advance price announcements may help suppliers coordinate onto their preferred equilibrium of posting the monopoly price.
Keywords: C71; C78; L13; L41; 330